ANALYSIS OF INACCURACY OF THE DIRECT MEASUREMENTS OF THE POSITIONS COSMIC OBJECT - Paltsev, N. G.; Kolesnik, S. Ya. (Одеські астрономічні публікації, 2017)
On base of the analysis to coordinate information, got at observations of the positions of the stars on cinema-theodolite KT-50, cross bar-beam which is not allowed, is designed algorithm and is organized a study of the instrument. The Certain values, characterizing coordinate system KT- 50: - a zero-points of the scales of the azimuth and heights, of the collimation, slopping to horizontal axis, slopping to vertical axis and its azimuth. The Designed algorithm of the calculation of the adjustments counting out the azimuth and heights as of processing the frames CCD-observations.